INVESTIGATION ON FINITE ELEMENT MODELING METHOD OF WITH TRIPLE JUNCTION POLYCRYSTALLINE INTERGRANULAR FRACTURE - SHI JunLin; ZHAO JianPing (Jixie qiangdu)
Cohesive zone model was used to simulate polycrystalline intergranular fracture at the grain level model,the finite element model build-ing reflected the actual situation is a difficult point.In this paper,Mixed Programming of Matlab,Python and Abaqus,An algorithm was presented which can easily and quickly generated Voronoi geometric model and the grain sizes distribution agrees with lognormal distribution.Realized the automatically insert the zero-thickness cohesive interface element by writing nodes and elements at crystal boundary,firstly solved the void zone at the intersection of the three zerothickness cohesive element,which is the triple junction,And to make up the defect of cohesive zone model.The whole process of the finite element analysis was performed automatically by secondary development,including the assignation material properties,material orientation,load application,model solution.Finally,polycrystalline aluminum was used as an example to simulate the intergranular fracture process without the initial damage.The results show that the method is more effectively and practically,which can be used to simulate polycrystalline intergranular crack initiation and propagation in random microscopic grains.